Historical dictionary of Mormonism - Bitton, Davis, 1930-2007.; Alexander, Thomas G., 1935- (Lanham, Md. : Scarecrow Press, 2008)
Provides a chronology, an introductory essay, a bibliography, and hundreds of cross-referenced dictionary entries on crucial persons, organizations, churches, beliefs, and events within the Mormon religion.
Introduction -- The dictionary -- Church presidents -- The family : a proclamation to the world -- Temples dedicated through February 2008 -- The living Christ : the testimony of the apostles of the Church of Jesus Christ of Latter-day Saints.
Includes bibliographical references.
Print version record.
Keywords: Mormon Church -- Dictionaries; Mormons -- Biography -- Dictionaries; Mormon Church; Mormons; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Christianity / Denominations; Biography -- Dictionaries; Dictionaries; Electronic books